Analytical study between Greek and Roman furniture (Al-Academy, 2025)
With time and the different ages, furniture has emerged in various forms, bearing the features of the age that belongs to it. Despite numerous studies and encyclopedias that confine the features of each era's furniture, there is still some confusion about the furniture of the Greek era. The study aims to analyze Greek-era and Roman-era furniture, learn the factors that influence the emergence of features of each age's furniture, and make comparisons between them. The study followed the historical and analytical descriptive curriculum. One of the most important findings of the research is that there is a difference between the features of Greek-era furniture and Roman-era furniture. Political, economic, environmental, and religious factors impact the features of Greek and Roman-era furniture; among the most important research recommendations is to increase studies on the features and characteristics of Roman and Greek furniture to find out the differences between them